God and Ethics - Baggett, David (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This unique reprint was the culmination of a Special Issue of the journal Religions with a focus on "God and Ethics," a topic both rich in historical significance and of special contemporary importance in light of the recent resurgence of interest in this branch of natural and philosophical theology, the philosophy of religion, and religious epistemology. Suggested themes for the reprint included whether or not the evidence furnished by various aspects of ethics points in the direction of God, and, if so, in what fashion; discussion of obstacles in the way of theistic ethics; and challenges in making the best sense of ethics apart from theism. It was suggested in the original call for papers that the nature of the moral evidence adduced might cover (but was not limited to) intrinsic human value, binding moral obligations, moral knowledge, moral transformation, the category of evil, issues associated with reconciling moral reasoning and prudential reasoning, and the historical discussion of moral atheology or the moral argument. Matters of the roles of reason and emotion in moral epistemology, the nature of potential dependence relations of morality on God, and what a sufficiently robust moral theology looks like were all topics for investigation rife with potential. The ten contributions that passed muster by surviving the peer-review process did not disappoint, and they now comprise this collection, making for an exciting contribution to the literature. We are deeply grateful to all of the excellent contributors and to all the good folks at Religions for everything they have done to make this volume possible.